2019
DOI: 10.1002/pros.23836
|View full text |Cite|
|
Sign up to set email alerts
|

IL‐8 protects prostate cancer cells from GSK‐3β‐induced oxidative stress by activating the mTOR signaling pathway

Abstract: Introduction Both oxidative stress and inflammation play important roles in prostate cancer cell apoptosis or proliferation; however, the mechanisms underlying these processes remain unclear. Thus, we selected interleukin‐8 (IL‐8) as the bridge between inflammation and cancer cell oxidative stress‐induced death and aimed to confirm its connection with mTOR and Glycogen synthase kinase‐3 beta (GSK‐3β). Methods We overexpressed GSK‐3β and observed its effect on reactive oxygen species (ROS) and oxidative stress‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…The results indicated that the AKT-mTOR signaling pathway may participate in the process of N-cadherininduced increase in FFA production (figure 6D), which is in agreement with the research of Kumagai et al 40 Because we confirmed that IL-8 was regulated by N-cadherin, and our previous research showed that IL-8 can activate AKT/GSK-3β, 43 we hypothesized that N-cad-KO can downregulate IL-8 expression and then block the AKT-mTOR pathway. First, we determined whether IL-8 knockout can decrease the expression of JAK-1, and the data shown in online supplemental figure 7A indicated that JAK-1 expression did not change after the IL-8 knockout.…”
Section: N-cadherin Knockout Eliminates the Metabolic Advantage Of Trsupporting
confidence: 92%
See 1 more Smart Citation
“…The results indicated that the AKT-mTOR signaling pathway may participate in the process of N-cadherininduced increase in FFA production (figure 6D), which is in agreement with the research of Kumagai et al 40 Because we confirmed that IL-8 was regulated by N-cadherin, and our previous research showed that IL-8 can activate AKT/GSK-3β, 43 we hypothesized that N-cad-KO can downregulate IL-8 expression and then block the AKT-mTOR pathway. First, we determined whether IL-8 knockout can decrease the expression of JAK-1, and the data shown in online supplemental figure 7A indicated that JAK-1 expression did not change after the IL-8 knockout.…”
Section: N-cadherin Knockout Eliminates the Metabolic Advantage Of Trsupporting
confidence: 92%
“…58 IL-8 inhibition was achieved as previously described. 43 Briefly, cells were transfected with 100 nM DNA single clone plasmids containing a shRNA to silence IL-8 (category number C01001; GenePharma, Shanghai, China) using the transfection reagent Lipofectamine 3000 (Invitrogen, Carlsbad, California, USA) according to the manufacturer's instructions.…”
Section: Cell Culture and Cell Treatmentmentioning
confidence: 99%
“…Sun et al [49] concluded that mTOR inhibits the expression of glycogen synthase kinase-3 (GSK-3) in prostate cancer cells. The down-regulation of GSK-3 will inhibit the caspase-3 signaling pathway, leading to the reduction of ROS production.…”
Section: Autophagy and Apoptosis Of Cancermentioning
confidence: 99%
“…GSK-3 is therefore a part of the canonical β-catenin/Wnt pathway, which signals the cell to divide and proliferate [ 156 ]. In prostate cancer cells , IL-8 is able to increase GSK-3β phosphorylation at Ser9 and thus attenuates its activity through an mTOR mediated mechanism [ 157 ].…”
Section: Interleukin 8—a Major Key-player In CM Pathogenesismentioning
confidence: 99%